Soundings : the story of the remarkable woman who mapped the ocean floor - Felt, Hali. (New York : Henry Holt and Co., 2012)
A portrait of the enigmatic geologist who was the first person to map the ocean floor describes her battles against sexism, the artistry and science that informed her work, and her contributions to the establishment of the Lamont Geological Observatory.
Includes bibliographical references (p. [303]-321) and index.
Keywords: Tharp, Marie; Cartographers -- United States -- Biography; Geomorphologists -- United States -- Biography; Women cartographers -- United States -- Biography; Submarine topography